2013
DOI: 10.1136/gutjnl-2013-305138
|View full text |Cite
|
Sign up to set email alerts
|

Phase IIb multicentred randomised trial of besifovir (LB80380) versus entecavir in Asian patients with chronic hepatitis B

Abstract: Background Besifovir (LB80380) is an acyclic nucleotide phosphonate effective in hepatitis B virus (HBV) DNA suppression for both treatment-naive and lamivudine-resistant chronic hepatitis B (CHB) patients in preliminary studies. Design We aimed to compare the safety and antiviral activity of two doses of besifovir (90 mg and 150 mg daily) with entecavir 0.5 mg daily in CHB patients. 114 patients were randomised to receive besifovir 90 mg daily (n=36), besifovir 150 mg daily (n=39) or entecavir 0.5 mg daily (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 15 publications
1
52
0
Order By: Relevance
“…Pradefovir (44), invented by Metabasis Therapeutics, is a prodrug that targets adefovir to the liver for the treatment of hepatitis B and is in Phase II clinical trials [114,[120][121]. Besifovir (45, LB80380), invented by LG Chem Ltd, is an acyclic nucleotide phosphonate with chemical similarity to adefovir and tenofovir, which has completed the clinic safety and efficacy study in the patients with lamivudine-refractory chronic hepatitis B, bioequivalence of LB80380 free base and maleate salt tablets and safety and efficacy study of LB80380 in the treatment-naive patients of chronic hepatitis B [122][123][124][125][126][127]. Tenofovir alafenamide (46, TAF; GS-7340), invented by Gilead Sciences, is a prodrug of TDF and achieves higher active metabolite concentrations in peripheral blood mononuclear lymphocytes and lymphatic tissues [128][129][130][131].…”
Section: Inhibitors Of Viral Dna Synthesismentioning
confidence: 99%
“…Pradefovir (44), invented by Metabasis Therapeutics, is a prodrug that targets adefovir to the liver for the treatment of hepatitis B and is in Phase II clinical trials [114,[120][121]. Besifovir (45, LB80380), invented by LG Chem Ltd, is an acyclic nucleotide phosphonate with chemical similarity to adefovir and tenofovir, which has completed the clinic safety and efficacy study in the patients with lamivudine-refractory chronic hepatitis B, bioequivalence of LB80380 free base and maleate salt tablets and safety and efficacy study of LB80380 in the treatment-naive patients of chronic hepatitis B [122][123][124][125][126][127]. Tenofovir alafenamide (46, TAF; GS-7340), invented by Gilead Sciences, is a prodrug of TDF and achieves higher active metabolite concentrations in peripheral blood mononuclear lymphocytes and lymphatic tissues [128][129][130][131].…”
Section: Inhibitors Of Viral Dna Synthesismentioning
confidence: 99%
“…Besifovir (LB80380) is a NUC that has been shown to have antiviral activity against both wild-type virus and virus with drug resistance mutations [83]. Studies have shown it to be well-tolerated and effective at reducing viral load in CHB patients with lamivudine-resistant virus [84] and non-inferior to entecavir 0.5 mg daily in treatment-naive CHB patients [85]; the only significant adverse effect of besifovir was l -carnitine depletion that required carnitine supplementation [85]. AGX-1009, a prodrug of TDF that is activated by a different molecular side chain, has demonstrated good efficacy for inhibition of viral replication in preclinical studies and is currently being studied in a phase I trial in China [86].…”
Section: Direct-acting Antiviralsmentioning
confidence: 99%
“…In the present treatment paradigm, new-generation drugs such as tenofovir alafenamide and besifovir may have similar efficacy with fewer adverse effects [73, 85, 182]. However, the ultimate goal of chronic HBV treatment would be the elimination of cccDNA [181, 182].…”
Section: Novel Therapiesmentioning
confidence: 99%
“…Besifovir (LB80380) is a novel and potent guanosine analogue with rapid intracellular phosphorylation to inhibit HBV replication. It also has potent anti‐HBV activity, irrespective wild type virus or virus resistant to approved nucleos(t)ide analogues . In a multicenter randomised trial, there were no differences in the efficacy of viral suppression and HBeAg seroconversion between besifovir and entecavir therapy .…”
Section: Novel Approaches: Direct Acting Anti‐virals (Daa)mentioning
confidence: 99%